2019
DOI: 10.22435/mpk.v29i3.1460
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Anopheles dalam Ekosistem Hutan dan Resiko Terjadinya Penularan Malaria di Beberapa Provinsi di Indonesia

Abstract: Forests are ecosystems that can support the existence of malaria vectors. The discovery of vector species in the forest environment will increase malaria transmission in the forest and its surroundings. The provinces of South Sumatra, Central Java, Central Sulawesi, and Papua are some of the provinces in Indonesia that still have forest ecosystems. The aim of the study was to know the diversity of Anopheles species and risk of malaria transmission in forest ecosystems in the provinces of South Sumatra, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…vagus live in rice fields [12]. Many studies of malaria vector showed the habitat of Anopheles are from mountains, forest, and coastal areas [19]. The potential of Anopheles spp breeding sites in West Nusa Tenggara were discovered near the shore, including lagoons, rivers, and rice paddies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…vagus live in rice fields [12]. Many studies of malaria vector showed the habitat of Anopheles are from mountains, forest, and coastal areas [19]. The potential of Anopheles spp breeding sites in West Nusa Tenggara were discovered near the shore, including lagoons, rivers, and rice paddies.…”
Section: Resultsmentioning
confidence: 99%
“…sundaicus. Those spesies are distributed in wide range of ecosystems, from mountains, forest to coastal area [19,[21][22][23][24][25]. A study in Papua showed that larva An.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in Keerom Papua, environments featuring shrubs and stagnant water near houses were identified as major malaria risk factors, and residential proximity to forests was also linked to increased malaria risk (33). The existence of forests near residential areas also poses a risk of transmitting malaria (34). The risk of malaria transmission is related to the presence of Anopheles sp.…”
Section: Discussionmentioning
confidence: 99%
“…aconitus yang merupakan vektor malaria. 14 Untuk mengetahui penanganan pengendalian malaria, maka dilakukan round table discussion.…”
Section: Pendahuluanunclassified